The effect of sample processing parameters on breakdown properties of polyethylene and polypropylene blends - Nor Hashimah Ismail, 1983-, author 629577; Lau, Kwan Yiew, supervisor 627362; Fakulti Kejuruteraan. Sekolah Kejuruteraan Elektrik 619066 (Johor Bahru, Johor : Universiti Teknologi Malaysia, 2020)
Thesis (Sarjana Kejuruteraan (Elektrik Kuasa))